PERAN MOTIVASI KERJA DAN DUKUNGAN SUAMI TERHADAP STRES KONFLIK PERAN GANDA DAN KEPUASAN PERKAWINAN - Eva Meizara Puspita Dewi; Abdul Saman (Psympathic : Jurnal Ilmiah Psikologi, 2010)
The purpose of this research was to analize (1) the impact of work motivation to conflict stress caused by doble roles on career women, (2) the effect of spouse support to conflict stress caused by doble roles on career women, (3) the influence of spouse support to marriage contentment on career women, and (4) The influence of conflict stress of doble roles on career women and their marriage contement. This research employed quantitatif approch. There were 30 employees of BNI Makassar branch taken as subjects based on purposive sampling method. The 4 scale research instrument was applied while regression program of SPSS windows 14.00 was employed to analize the data. Study found that (1) there were negative impact of work motivation to conflict stress of doble roles on career women (r=0,436), (2) there were negatif effect of spouse support to conflict stress caused by doble roles on career women (r=0,745), (3) there were positif influence of spouse support to marriage contentment on career women (r=0,645), and (4) there were negative influence of conflict stress of doble roles on career women and their marriage contement (r=0,429).